The Transactions Demand for Money in the Presence of Currency Substitution: Evidence from Vietnam. - Adam, C; Goujon, M; Jeanneney, S (Routledge, 2004)
Currency substitution - the use of foreign money to finance transactions between domestic residents - is widespread in low income and transition economies. Traditionally, however, empirical models of the demand for money tend to concentrate on the portfolio motive for holding foreign currency, while maintaining the assumption that the income elasticity of demand for domestic money is invariant to the degree of currency substitution. A simple re-specification of the demand for money is offered which more accurately reflects the process of currency substitution by allowing for a variable income elasticity of demand for domestic money. This specification is estimated for Vietnam in the 1990s. Using a standard cointegration framework evidence is found for currency substitution only in the long-run but well-defined wealth effects operating in the short-run.